2014
DOI: 10.1002/jmv.23974
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neuraminidase inhibitors on the release of oseltamivir-sensitive and oseltamivir-resistant influenza viruses from primary cultures of human tracheal epithelium

Abstract: Defining the effects of neuraminidase inhibitors on influenza virus infection may provide important information for the treatment of patients. The effects of neuraminidase inhibitors have been examined using various methods, including viral release from kidney cells. However, the effects of neuraminidase inhibitors on viral release from primary cultures of human tracheal epithelial cells, which retain functions of the original tissues, have not been studied. The effects of neuraminidase inhibitors on the repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In this report, we found that the NA segment of H9N2 AIV modulated the immune function of DCs by adjusting miR-155 and miR-674 expression. NA, an envelope glycoprotein on the surface of the influenza virus, catalyses the cleavage of sialic acids on glycoproteins from virus-infected cells and enables virus release [18, 19]. Studies have demonstrated that low NA enzyme activity renders virus release from infected cells inefficient and leaves progeny viruses gathered on the cell surface [19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we found that the NA segment of H9N2 AIV modulated the immune function of DCs by adjusting miR-155 and miR-674 expression. NA, an envelope glycoprotein on the surface of the influenza virus, catalyses the cleavage of sialic acids on glycoproteins from virus-infected cells and enables virus release [18, 19]. Studies have demonstrated that low NA enzyme activity renders virus release from infected cells inefficient and leaves progeny viruses gathered on the cell surface [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…NA, an envelope glycoprotein on the surface of the influenza virus, catalyses the cleavage of sialic acids on glycoproteins from virus-infected cells and enables virus release [18, 19]. Studies have demonstrated that low NA enzyme activity renders virus release from infected cells inefficient and leaves progeny viruses gathered on the cell surface [19, 20]. DCs represent a central element in the generation and maintenance of immune responses [21].…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir-resistant influenza A (H1N1) virus infection has been reported, and this type of seasonal influenza has caused severe disease in immuno-compromised patients [26]. In a previous study, Oseltamivir did not reduce inflammatory cytokine production by airway epithelial cells after infection with seasonal influenza viruses with an Oseltamivir-resistant genotype [27]. Moreover, Oseltamivir did not reduce viral titers or viral RNA levels.…”
Section: Clinical Features Of Influenza Virus Infection and Antiinflumentioning
confidence: 97%
“…Moreover, Oseltamivir did not reduce viral titers or viral RNA levels. The 50% inhibitory concentration (IC 50 ) of Oseltamivir for neuraminidase activity in the Oseltamivir-resistant seasonal virus was 300-fold higher than that observed for the pandemic influenza virus [27]. According to a report by Shobugawa et al, oral intake of Oseltamivir is feasible for children younger than 5 years old, whereas Zanamivir inhalation is prescribed for children ≥ 5 years old [28].…”
Section: Clinical Features Of Influenza Virus Infection and Antiinflumentioning
confidence: 99%
See 1 more Smart Citation